(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2019)
Twenty-two essential oil samples from Germany and Albania were assayed to test their inhibitory and fungicidal activity against Cryphonectria parasitica (Murr.) Barr., the major causal agent of chestnut blight on chestnut trees, using the fumigant macrodilution method. Test concentrations of the oils in air phase were: 0.02, 0.04, 0.08, 0.16 and 0.32 μl ml-1, and minimum inhibitory and fungicidal concentrations were determined. The strongest activity was shown by two samples of mint oil from Germany and Albania, and black pine at the concentration of 0.02 μl ml-1 of air for both test isolates (M1 and 4S). The tested plant essential oils also included: eucalyptus, sage, silver fir and cade. Only three samples of EOs (mint (2) and black pine) were lethal to both isolates. Sage and silver fir oils were more toxic to the M1 isolate, while cade and eucalyptus oils were more toxic to the 4S isolate. Fifteen oils: mint (2), black pine, cade, eucalyptus, silver fir, sage, pine (4), oregano, lavender, and rosemary (2), inhibited the growth of Cryphonectria parasitica, and seven oils (two samples of mint, eucaliptus, black pine, sage, silver fir and cade) showed fungicidal effects on the pathogen.